2006
DOI: 10.1111/j.1365-2664.2006.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic restoration of a stocked brown trout Salmo trutta population using microsatellite DNA analysis of historical and contemporary samples

Abstract: Summary1. Gene flow from domesticated to wild populations is a major threat to wild salmonid fish. However, few studies have addressed how populations could be restored after admixture has occurred. We analysed the prospects for restoring the previously intensively stocked brown trout population of the Skjern River, Denmark, by identifying remaining nonadmixed individuals to be used for supportive breeding. 2. We analysed microsatellite DNA markers in historical (1940 -50s) and contemporary (1992)(1993)(1994)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 52 publications
3
36
0
Order By: Relevance
“…This range of admixture values is similar to that applied in other conservation studies to define 'purebred' individuals (Beaumont et al 2001;Vähä and Primmer 2006). However, in situations where backcross specimens might be present, this approach carries the danger of misclassifying post F1-hybrids as purebreds (Hansen et al 2006;Vähä and Primmer 2006;Meraner et al 2008). For this reason, an alternative analytical approach implemented in the ONCOR software ) was applied to assign individuals to groups and obtain a relative probability of assigning an individual to a particular group (marble trout, hybrid and brown trout).…”
Section: Admixture Analysis and Identification Of Remnant Populationssupporting
confidence: 64%
See 1 more Smart Citation
“…This range of admixture values is similar to that applied in other conservation studies to define 'purebred' individuals (Beaumont et al 2001;Vähä and Primmer 2006). However, in situations where backcross specimens might be present, this approach carries the danger of misclassifying post F1-hybrids as purebreds (Hansen et al 2006;Vähä and Primmer 2006;Meraner et al 2008). For this reason, an alternative analytical approach implemented in the ONCOR software ) was applied to assign individuals to groups and obtain a relative probability of assigning an individual to a particular group (marble trout, hybrid and brown trout).…”
Section: Admixture Analysis and Identification Of Remnant Populationssupporting
confidence: 64%
“…In addition, the marble trout population from Passer/Passirio showed significant genetic differentiation to all other South Tyrolean marble trout samples and should therefore be managed as a distinct conservation unit (F ST values up to 0.11, significant at the 0.001 level; Appendix 2, see Table 5). Since comparatively low F ST values of 0.02 can be associated with substantial ecological differences between some salmonid populations (Waples et al 2004;Hansen et al 2006), a certain marble trout breeding strain should be stocked only in the river (and its closest tributaries) where the respective founder specimens came from. This is important to maintain original microgeographic population patterns.…”
Section: Directionality Of Introgression and Potential Factors Delayimentioning
confidence: 99%
“…Reproductive isolation through isolation by time (IBT) has recently attracted considerable interest (Hendry & Day 2005). IBT may be common in hatchery-wild salmonid interactions, as genetic components of spawning time differences have been demonstrated in at least one species (Sakamoto et al 1999), hatchery managers often select broodstock for early spawning (Hansen et al 2006) and temporal segregation of spawning has been observed in sympatric wild and hatchery strain salmonids (Shields et al 2005). We hypothesize that IBT has rescued a small proportion of the indigenous SKJ population from full introgression.…”
Section: Discussionmentioning
confidence: 99%
“…Wang (2003) presents a maximum likelihood approach, implemented in the program Leadmix, which estimates the contribution of two or more parental populations to an admixed population, taking into account genetic drift in the parental and admixed populations since the hybridization event. This approach is highly applicable to the situation considered here, and has been used to investigate admixture involving two parental groups in several taxa (Larsen et al 2005;Belle et al 2006;DeKoning et al 2006;Hansen et al 2006). However we found Leadmix to be extremely computationally intensive: for most populations tested we terminated the program after it had been running on a fast personal PC for several weeks, but before it had reached a solution.…”
Section: Utility Of Alternative Approaches For Investigation Of Admixmentioning
confidence: 99%